(untitled) (Archive of Conferences, 2021)
The effectiveness of systemic administration of TLP in the acute period of myocardial infarction was studied and the effect of these drugs on the dynamics of myoglobin (MG) was studied in order to further predict the course of the acute period of myocardial infarction. The study included 126 patients aged 18 to 45 years. The average age of the patients was 31.5 ± 5 years. Among these patients, TLT was performed in 72 patients with AMI who were admitted to the cardiac intensive care unit of the SF RSCEMP in the first 6 hours of illness.